Produção de leite de vacas Guzerá de corte e sua associação com as DEPs de seus pais - Paulo Henrique Silva Guimaraes (2010)
The milk yield of 59 primiparous Guzera cows was evaluated by two methods of hand milking, with (O+) and without (O-) use of oxytocin. The cows that were mated with Guzerá and Holstein bulls, calved between days 06/05/2006 and 02/05/2007 and milk production was measured every two weeks from 07/13/2006 to 07/14/2007. It was evaluated the weight at 205 days (P205a) of the calves and the correlation of this measure with the milk yield in each treatments. The milk yield at 205 days (Lac205a) in treatment O+ was 994 kg (4.85 kg/cow/day), more than twice the production in the O- treatment (493.5 kg = 2.41 kg/cow/day). The weight of calves at 205 days was 173.3 kg. The correlation between Lac205a for the treatment O+ and Lac205a for O- treatment was 0.59 (p <0.0001), between Lac205a O+ and P205a 0.44 (p <0, 0004) and between Lac205a O- and P205a 0.29 (p <0.0229).